Atypical Presentations of Paediatric Tuberculosis: A Series of Seven Cases from a Tertiary Care Centre in South India - Rakshitha S Prasad; Mithila Das Mazumder; E Shruthy; Gurram Hasvitha; SL Akhila Swaraj (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Paediatric Tuberculosis (TB) remains one of the leading infectious causes of illness and death among children globally, with diverse clinical manifestations that often complicate diagnosis and management. This case series describes seven children aged nine months to 13 years who presented with atypical or extrapulmonary manifestations of TB at a tertiary care centre in South India. Diagnosis was based on a combination of clinical features, radiological findings, microbiological evidence (CBNAAT/GeneXpert, histopathology), and therapeutic response to Anti-Tubercular Therapy (ATT). The spectrum included Central Nervous System (CNS) tuberculoma presenting with seizures, calvarial TB with epidural extension, endobronchial TB mimicking acute severe asthma, tuberculous pleural effusion, pulmonary TB associated with Severe Acute Malnutrition (SAM), Pott’s disease with paravertebral abscess, and disseminated TB with hepatic abscesses in infancy. Microbiological confirmation was obtained in selected cases, while others required clinicoradiological correlation. All children showed clinical improvement following initiation of ATT, supported by nutritional rehabilitation, corticosteroids, or surgical intervention when indicated. This series highlights the broad clinical spectrum of paediatric TB and underscores the importance of high clinical suspicion and early imaging to prevent diagnostic delays and long-term sequelae.